Board of Directors and ownership structure: a study on small and medium enterprises (SMEs) in Malaysia - Takiah Mohd Iskandar,; Nor Hazwani Hassan,; Zuraidah Mohd Sanusi,; Zakiah Muhammadun Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Small- and medium-sized enterprises (SMEs) do not gain sufficient economic returns despite their significant economic contributions. A possible cause of poor SME performance is weak corporate governance. However, the corporate governance of SMEs is rarely investigated. Ownership structure provides SMEs with a monitoring mechanism that enhances performance. This study examines the relationships between board characteristics (including size, composition boards, CEO duality, expertise, and ethnicity) and SME performance in Malaysia. This study also explores how such relationships can be moderated by monitoring ownership structure. Survey results on SMEs in Klang Valley and Selangor areas show that non-executive boards and CEO duality are significantly and positively related to firm performance. In comparison, management ownership is significantly and negatively related to performance. Board size, expertise, ethnicity, and family ownership are not significantly related to SME performance. Findings indicate that good corporate governance improves decision making and firm performance. Furthermore, agency theory can explain conflict of interest in SMEs and the importance of corporate governance in enhancing their performance.